Financial Capability and Financial Behavior among people in Surabaya - Wiryakusuma, I Gusti Bagus Yosia; Handijaya, Elizabeth Maeko Cyrilla (Excellent, 2023)
This research aims to see how gender differs in the financial capability and financial behavior of people in Surabaya. The number of respondents in this study was 204 people. The criteria for respondents in this study were to be over 17 years old and domiciled in Surabaya. The method used in this research is the independent t test and ANOVA test. The results found from this research are that there are differences in the financial capability of men and women. Men are said to be better in financial capability than women. Apart from that, the results also found that there were no differences in the financial behavior of men and women. This research also found something else, namely that the higher a person's financial capability, the better that person's financial behavior will be.